IMPLEMENTASI MODEL CREATIVE PROBLEM SOLVING DALAM MENINGKATKAN KEMAMPUAN METAKOGNITIF, PEMECAHAN MASALAH, PEMAHAMAN MATEMATIS DAN SELF-REGULATED LEARNING SISWA SMA : Penelitian Kuasi Eksperimen pada Salah Satu Sekolah Menengah Atas di Kabupaten Ciamis - Adang, Effendi (2018)
This study aims to describe the improvement of metacognitive ability, mathematical problem solving, mathematical understanding, and self-regulated learning of high school students who acquired CPS learning and direct learning (DL). This research uses quasi-experimental method with nonequivalent control-group design. The population of all students of grade X in one of high schools in Ciamis City, the sample of students of grade X.The conclusions of this study are : (1) Student enhancement in metacognitive ability learning with higher CPS from students who studied with DL, (2) There is no difference in metacognitive ability between students who are in high, medium, and low group of Priot Mathematical Knowledge (PMK) students; (3) There is no interaction effect between learning model and PMK on enhancement of metacognitive ability; (4) There is no difference enhancement metacognitive ability between students studying with CPS and students studying with DL based on PMK factors; (5) There is no difference in problem-solving abilities between students studying with CPS and students studying with the DL; (6) There is no difference in problem solving ability among high, medium and low PMK students; (7) There is no interaction effect between learning model and PMK on problem solving ability; (8) There is no difference in problem-solving abilities between students studying with CPS and students studying with DL based on PMK factors; (9) Enhancement of mathematical understanding of students who study with CPS is higher than students studying with the DL; (10) There is no difference in the enhancement of mathematical understanding among high, low, and low PMK students; (11) There is no interaction effect between learning model and PMK on students' mathematical understanding ability; (12) There is no difference in the enhancement of mathematical understanding among students studying with CPS and students studying with DL based on PMK factors; (13) The students' enhancement in self-regulated learning ability who worked under CPS is higher than students who worked under DL; (14) There is no difference in the enhancement of self-regulated learning ability with PMK.;---Penelitian ini bertujuan untuk mendeskripsikan tentang peningkatan kemampuan metakognitif, pemecahan masalah matematis, pemahaman matematis, dan self-regulated learning siswa SMA yang memperoleh pembelajaran CPS dan pembelajaran langsung (PL). Penelitian ini menggunakan metode kuasi-eksperimen dengan desain nonequivalent control-group. Populasinya seluruh siswa Kelas X pada salah satu SMA di Kota Ciamis, sampelnya siswa kelas X. Dari penelitian ini diperoleh kesimpulan, (1) Peningkatan kemampuan metakognitif yang belajar dengan CPS lebih tinggi dari siswa yang belajar dengan PL; (2) Tidak terdapat perbedaan peningkatan kemampuan metakognitif antara siswa KAM tinggi, sedang, dan rendah; (3) Tidak ada pengaruh interaksi antara model pembelajaran dengan KAM terhadap peningkatan kemampuan metakognitif; (4) Tidak terdapat perbedaan Peningkatan kemampuan metakognitif antara siswa yang belajar dengan CPS dan siswa yang belajar dengan PL berdasarkan faktor KAM ; (5) Tidak terdapat perbedaan peningkatan kemampuan pemecahan masalah antara siswa yang belajar dengan CPS dan siswa yang belajar dengan PL; (6) Tidak terdapat perbedaan peningkatan kemampuan pemecahan masalah antara siswa KAM tinggi, sedang, dan rendah; (7) Tidak ada pengaruh interaksi antara model pembelajaran dengan KAM terhadap kemampuan pemecahan masalah; (8) Tidak terdapat perbedaan peningkatan kemampuan pemecahan masalah antara siswa yang belajar dengan CPS dan siswa yang belajar dengan PL berdasarkan faktor KAM; (9) Peningkatan kemampuan pemahaman matematis siswa yang belajar dengan CPS lebih tinggi dari siswa yang belajar dengan PL; (10) Tidak terdapat perbedaan peningkatan kemampuan pemahaman matematis antara siswa KAM tinggi, sedang, dan rendah; (11) Tidak ada pengaruh interaksi antara model pembelajaran dengan KAM terhadap kemampuan pemahaman matematis; (12)Tidak terdapat perbedaan peningkatan kemampuan pemahaman matematis antara siswa yang belajar dengan CPS dan siswa yang belajar dengan PL berdasarkan faktor KAM; (13) Peningkatan kemampuan self-regulated learning siswa yang belajar dengan CPS lebih tinggi dari siswa yang belajar dengan PL; (14) Tidak terdapat perbedaan peningkatan kemampuan self regulated learning dengan KAM.